Report on the Nossimoddei-Aru Valley : irrigation in the Northern Province, Vavuniyan-Vilankulam district[s] - Parker, Henry, Irrigation Officer, Sri Lanka (Sessional papers, 1886)
Report submitted to the Parliament of Sri Lanka.